Avaliação da codisposição de resíduos de fossa e tanque sépticos em sistema de tratamento de esgoto composto por lagoas anaeróbias, facultativas e de maturação - Haddad, Katia Bittar (2013)
The deficiency displayed by public basic sanitation systems in Brazil forces a major part of the population to seek individual alternatives to the final treatment and disposal of domestic septage such as septic tanks and rudimentary cesspools. Waste coming from such individual systems are, for the most part, discharged into Waste Water Treatment Plants (WWTPs), which are not designed to such end. Hence, we observe a decrease in the efficiency of sanitary waste treatment by WWTPs, which, in turn, leads to the pollution of water resources. Thus, the present study aimed to assess the impacts caused by waste discharge from cesspools and septic tanks into an anaerobic lagoon, followed by a facultative and maturation lagoons. Barro Preto WWTP has two modules of stabilizing lagoons (A and B). Module A was utilized as evidence. In other words, it did not receive cesspool and septic tank waste discharge. Module B rate was 0.20%. In order to force the system, the WWTP total flow was deviated to module B and the volumetric flow rate yielded was 0.05%. To characterize sludge yield in the Trindade-GO municipality, composite samples from six septage haulers were collected. Parameter analyses were: PH, Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), solid series (TSS,VSS, FSS,TS,TVS,TFS), oils and grease, total Kjedhal nitrogen, amonniacal nitrogen, phosphorus and Escherichia coli. Sludge deposit bathymetry was conducted in the anaerobic lagoons and surface scum bulk was collected and quantified. To assess the interference of co-treatment in the performance of stabilizing lagoons simple samples were collected from the anaerobic, facultative and maturation lagoons. Parameters analyzed were: PH, BOD, COD, settleable solids ,total suspended solids, amonniacal nitrogen, phosphorus, oils and grease, total coliforms and E. coli. For the independent samples the t- Student test was applied in order to compare the values obtained from the lagoon effluents. In addition, results from maturation lagoons were compared with the Conama Resolution 430/2011 and the State Decree 1,745/1979.Statistically, no significant interference was observed in the co-treatment of cesspool and septic tank septage in the Barro Preto WWTP, except for settleable solids in the anaerobic lagoon effluents. Maturation lagoon effluents were in accordance with the Conama Resolution 430/2011 and State Decree 1,745/1979 requirements for analyzed parameters, with the exception of BOD, with yielded higher values in both modules over some periods of the study. The wastes from cesspool and septic tanks have characteristics similar to concentrated sewage pH raging between 5.3 and 8.4. COD/BOD ratio found was 3.92 mg.L-1, indicating that these residues are not found industries. The amount of scum collected from anaerobic lagoons was similar displaying an increase of 8% in sludge formation in the receiving lagoon. Hence, we concluded that Barro Preto WWTP is fit for the co-treatment of cesspool and septic tank septage disposal produced by the municipality of Trindade-GO. Furthermore, results show that anaerobic systems followed by facultative and maturation lagoons conforming to the same standards practiced by Barro Preto WWTP are fit to co-treat cesspool and septic tank septage.